Risk factors for symptomatic HIV‐associated neurocognitive disorder in adults aged 50 and over attending a HIV clinic in Tanzania. (20th July 2020) - Eaton, Patrick; Lewis, Thomas; Kellett‐Wright, Johanna; Flatt, Aidan; Urasa, Sarah; Howlett, William; Dekker, Marieke; Kisoli, Aloyce; Rogathe, Jane; Thornton, Jessica; McCartney, Judith; Yarwood, Vanessa; et al.
Abstract: Objectives: HIV‐associated neurocognitive disorder (HAND), although prevalent, remains a poorly researched cause of morbidity particularly in sub‐Saharan Africa (SSA). We aimed to explore the risk factors for HAND in people aged 50 and over under regular follow‐up at a government HIV clinic in Tanzania. Methods: HIV‐positive adults aged 50 years and over were approached for recruitment at a routine HIV clinic appointment over a 4‐month period. A diagnostic assessment for HAND was implemented, including a full medical/neurological assessment and a collateral history from a relative. We investigated potential risk factors using a structured questionnaire and by examination of clinic records. Results: Of the cohort (n = 253), 183 (72.3%) were female and the median age was 57 years. Fifty‐five individuals (21.7%) met the criteria for symptomatic HAND. Participants were at a greater risk of having symptomatic HAND if they lived alone [odds ratio (OR) = 2.566, P = .015], were illiterate (OR 3.171, P = .003) or older at the time of HIV diagnosis (OR = 1.057, P = .015). Age was correlated with symptomatic HAND in univariate, but not multivariate analysis. Conclusions: In this setting, HIV‐specific factors, such as nadir CD4 count, were not related to symptomatic HAND. The "legacy theory" of early central nervous system damage prior to initiation of anti‐retroviral therapy initiation may contribute, only in part, to a multifactorial aetiology of HAND in older people. Social isolation and illiteracy were associated with symptomatic HAND, suggesting greater cognitive reserve might be protective.